Ultra-Wideband Microstrip Bandpass Filter and Its Equivalent Circuit - Shita Fitria Nurjihan; Yenniwarti Rafsyam (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
Microstrip filters can be designed with various methods to obtain good performances, such as defected ground structure, open-ended slot, planar edge coupled, and split ring resonator with groundplane windowing. In this paper, the design of an ultra-wideband microstrip bandpass filter used the defected ground structure (DGS) method by adding a circular slot to the groundplane. The addition of the circular slot was carried out to improve the value of S parameter (return loss and insertion loss) from the initial filter design without a circular slot. In the simulation process, optimization was carried out by changing the value of filter component parameters such as patch length and thickness and circular slot width. The simulation results showed that the microstrip bandpass filter could pass frequencies in the range of 1.4 GHz to 5.7 GHz with the bandwidth response of 4.3 GHz. In addition, filter analysis could also be done with an equivalent circuit represented by lumped element components in the form of capacitors and inductors connected in series or parallel. The simulation results of the equivalent circuit had a wider bandwidth, which was able to pass frequencies in the range of 1.2 GHz to 6.1 GHz with a bandwidth response of 4.9 GHz.